The Role of Macrophage/B-Cell Interactions in the Pathophysiology of B-Cell Lymphomas - Pham, Lan V.; Pogue, Elizabeth; Ford, Richard J. (Frontiers in Oncology, 2018)
Macrophages (MPs) are heterogeneous, multifunctional, myeloid-derived leukocytes that are part of the innate immune system, playing wide-ranging critical roles in basic biological activities, including maintenance of tissue homeostasis involving clearance of microbial pathogens. Tumor-associated MPs (TAMs) are MPs with defined specific M2 phenotypes now known to play central roles in the pathophysiology of a wide spectrum of malignant neoplasms. Also, TAMs are often intrinsic cellular components of the essential tumor microenvironment. In concert with lymphoid-lineage B and T cells at various developmental stages, TAMs can mediate enhanced tumor progression, often leading to poor clinical prognosis, at least partly through secretion of chemokines, cytokines, and various active proteases shown to stimulate tumor growth, angiogenesis, metastasis, and immunosuppression. Researchers recently showed that TAMs express certain key checkpoint-associated proteins (e.g., programmed cell death protein 1, programmed cell death-ligand 1) that appear to be involved in T-cell activation and that these proteins are targets of other specific checkpoint-blocking immunotherapies (anti-programmed cell death protein 1/programmed cell death-ligand 1) currently part of new therapeutic paradigms for chemotherapy-resistant neoplasms. Although much is known about the wide spectrum and flexibility of MPs under many normal and neoplastic conditions, relatively little is known about the increasingly important interactions between MPs and B-lymphoid cells, particularly in the tumor microenvironment in patients with aggressive B-cell non-Hodgkin lymphoma (NHL-B). Normal and neoplastic lymphoid and myeloid cell/MP lineages appear to share many primitive cellular characteristics as well as transcriptional factor interactions in human and animal ontogenic studies. Such cells are capable of ectopic transcription factor-induced lineage reprogramming or transdifferentiation from early myeloid/monocytic lineages to later induce B-cell lymphomagenesis in experimental in vivo murine systems. Close cellular interactions between endogenous clonal neoplastic B cells and related aberrant myeloid precursor cells/MPs appear to be important interactive components of aggressive NHL-B that we discuss herein in the larger context of the putative role of B-cell/MP cellular lineage interactions involved in NHL-B pathophysiology during ensuing lymphoma development.